Structural characterization and immunomodulatory activity of polysaccharides from the flowers of Imperata cylindrica Beauv.var. major (Nees) C.E.Hubb - Honglin He; Haijun Huang; Yunheng Yang; Yi Liu; Ailing Liang; Yao Lei; Chenghuai Tang; Ling Yao; Zhiwei Chen (Chemical and Biological Technologies in Agriculture)
Abstract Background Polysaccharides are the main active components of Imperata cylindrica; however, research primarily targets its roots, with limited studies on flower-derived polysaccharides. Results Two polysaccharides, FIC-1 and FIC-2, were extracted from the flowers of Imperata cylindrica using water extraction and ethanol precipitation. They were characterized by FT-IR, HPGPC, and SEM, with FIC-1 undergoing additional methylation and NMR analysis. FIC-1 was a neutral polysaccharide with a molecular weight of 5.3 kDa, while FIC-2 was an acidic polysaccharide with a molecular weight of 23.3 kDa. The two polysaccharides had distinct surface morphologies: FIC-1 had a rough, flocculent structure, while FIC-2 was smooth and lamellar. FIC-1’s main chain consists of →4)-β-D-Glcp-(1→, α-D-Glcp-(1→, →3)-β-D-Galp-(1→, →5)-α-L-Araf-(1→, and →4,6)-α-D-Manp-(1→ linkages, with side chains mainly formed by α-L-Araf-(1→ linked at the O-4 position of →4,6)-α-D-Manp-(1→. Further analysis of FIC-1 indicated that it promoted M1 macrophage polarization, activated NF-κB signaling pathway, and enhanced glycolysis and phagocytosis. While FIC-1 did not directly kill cancer cells, the cytokine-rich medium from FIC-1-stimulated macrophages significantly inhibited the proliferation of LLC1, ID8, and Hepa1-6 cancer cells. Conclusions These findings provide useful evidence that support the development and potential clinical application of polysaccharides derived from the flowers of Imperata cylindrica. Graphical Abstract